Oxygen‐Insensitive Delayed Fluorescence Based on Singlet Manifold. Issue 5 (20th December 2022) - Wu, Yingnan; Zhao, Yanliang; Hou, Haoran; Hong, Gaobo; Guo, Yanhui; Zhang, Ruiling; Chen, Wenlong; Tian, Jiarui; Lv, Shibo; Wang, Honglei; Wang, Meishan; Wu, Chenyu; et al.
Abstract: Delayed fluorescence molecules have important applications in time‐resolved luminescence imaging (including lifetime imaging) systems. However, existing approaches of generating delayed fluorescence in organic molecules rely on triplets as long‐lived intermediate states. As such, this triplet‐based delayed fluorescence can be severely plagued by its oxygen sensitivity. As the presence of oxygen or ambient air can hardly be avoided in living biosystems, oxygen‐insensitive delayed fluorescence is highly desirable. Herein, a new pathway is reported for oxygen‐insensitive delayed fluorescence which is produced only within the singlet manifold. Such an example is found in a cyto‐compatible and water‐soluble trimethine cyanine dye C3T‐H, which bears a very high molar extinction coefficient and a narrow‐band red emission. It is demonstrated that this dye exhibits notable delayed fluorescence which cannot be diminished by the presence of oxygen or ambient air. Time‐resolved imaging of living cells in the presence of oxygen is successfully achieved. Through quantum chemical calculations, a nonemissive dark‐state structure in the S1 state is found to be thermodynamically viable (energy barrier ≈8 kcal mol −1 ) through the molecular twisting around the trimethine bridge of C3T‐H, which serves as a "reservoir" of the excitation energy to enable the oxygen‐insensitive delayed fluorescence. Abstract : Conventional delayed fluorescence relies on triplets as long‐lived intermediate states that are oxygen‐sensitive. Oxygen‐insensitive delayed fluorescence is presented in a cyanine dye in this work. A nonemissive dark‐state structure in the singlet state is found to be thermodynamically viable through molecular twisting, which serves as a "reservoir" of the excitation energy to enable the oxygen‐insensitive delayed fluorescence.